I saw Esau : the schoolchild's pocket book - Opie, Iona Archibald; Opie, Peter; Sendak, Maurice (Cambridge, Mass. : Candlewick Press, 1992)
A collection of rhymes and riddles traditionally passed on orally from child to child.
Keywords: Folk poetry, English; Children's poetry, English; English poetry -- Collections; Children's writings